Pelaksanaan Ikopin Mengabdi di Desa Cinta Damai Kecamatan Sukaresmi Kabupaten Garut - Evan Firdaus (E-Coops-Day : Jurnal Ilmiah Abdimas, 2026)
The IKOPIN Mengabdi program is a community service activity conducted by IKOPIN University students in Cinta Damai Village, Sukaresmi District, Garut Regency, over five days from November 22–26, 2025. This program aimed to improve the quality of life of rural communities through social, economic, educational, and environmental empowerment as a solution to face the era of digitalization 5.0. The implementation method employed a participatory approach, including observation, planning, implementation, and program evaluation. The program was divided into four main areas: (1) Cooperative Sector, through KDKMP socialization, technical guidance on cooperative administration and financial management, and socialization of creative economy based on social media; (2) Community Sector, through Pos to Pos activities and renovation of kobong (madrasah learning space); (3) Environmental Sector, through the establishment of a waste bank, reforestation of 60 tree seedlings in landslide-prone areas, and distribution of seedlings to 7 surrounding villages; and (4) Education Sector, through the development of a Literacy Corner and education on literacy, bullying prevention, and digital entrepreneurship. The results showed increased community understanding of cooperatives, strengthened capacity of KDKMP management, the establishment of a circular economy-based waste management system, increased children's reading interest, and enhanced student awareness of bullying and digital business opportunities. This program provided significant positive impacts on strengthening the social, economic, educational, and environmental capacities of the village. For sustainability, further mentoring and active community participation in managing the program independently are required.